On-line power system transient stability assessment using a regression model in contingency screening - Chheng, Monyvathna
The study develops a fast, simple and comprehensive technique for on-line power Transient Stability Assessment (TSA) for the case of fault disturbances in the power transmission system. A case study for preventive control by rescheduling the generation is included to describe how information given by TSA apply for determining control action. For TSA, we focus on implementation of the on-line Contingency screening method. We aim to build a regression model between the proposed index and the Critical Clearing Time (CCTs). This regression model is based on off-line calculations for application in the real-time Transient Stability Assessment. Three different indices are introduced; the first one is the rotor Angle Increment (AI), the second one is Absolute Angle Increment (AbAI) and the last one is (KeI) which is based on the Transient Kinetic Energy. There are two major part for the methodology; Off-line and On-line calculation. With the off-line computation, the regression model relationship between the indicates and CCT are built. For the on-line part, CCT will be determined by using the regression equation obtained from the off-line study. A case study of preventive control illustrates how the information obtained from our transient stability assessment is applied to derive a control action by using generation rescheduling to meet predefined target CCT. Finally, the IEEE 39-Bus 10-Machine System and the Cambodia Transmission System (CTS) are used for evaluating the accuracy of the proposed method.